Evaluation of the impact of human immunodeficiency virus pre-exposure prophylaxis on new human immunodeficiency virus diagnoses during the COVID-19 pandemic. (January 2022) - Keane, A; Regan, SO; Quinn, L; Murphy, D; Kelly, BO; Lynam, A; Lyons, F; Devitt, E
Aims: The national PrEP programme launched in Ireland in November 2019 with tenofovir/emtricitabine free to those meeting eligibility criteria. We assessed the impact of the first year of the PrEP programme on new HIV diagnoses in the largest sexual health and HIV service in Ireland. Methods: A free PrEP service was established in November 2019. We reviewed the number of new diagnoses of HIV between November 2018–2019, before the introduction of the national PrEP programme and compared this with the number of new HIV diagnosis between November 2019–2020. Results: There were 95 new HIV diagnoses (63.3% MSM) between November 2018 and 2019 and 73 new HIV diagnoses (65.7% MSM) between November 2019 and 2020. There was a statistically significant decline in new HIV diagnoses between the 2 years ( P = 0.0003). 546 patients were prescribed PrEP as of December 2020.106 patients (19.4%) changed their PrEP dosing regimen due to lockdown. 178 individuals (32.6%) had a rectal infection diagnosed. Conclusion: There has been a reduction in new HIV diagnoses in our cohort (although this has occurred during a global pandemic). It is too early to say if PrEP reduces late presentations of HIV based on our findings. A significant number of rectal infections were identified in the PrEP clinic suggesting ongoing risk despite pandemic restrictions. Further research into sexual practices during COVID-19 is needed to assess if this had an impact on the lower rates of HIV acquisition.